Health and Dental Insurance and Health Care Utilization Among Children, Adolescents, and Young Adults With CKD: Findings From the CKiD Cohort StudyPlain-Language Summary - Andrea R. Molino; Maria Lourdes G. Minnick; Judith Jerry-Fluker; Jacqueline Karita Muiru; Sara A. Boynton; Susan L. Furth; Bradley A. Warady; Derek K. Ng (Kidney Medicine, 2022)
Rationale & Objective: To understand the association between health and dental insurance status and health and dental care utilization, and their relationship with disease severity in a population with childhood-onset chronic kidney disease (CKD). Study Design: Observational cohort study. Settings & Participants: Nine hundred fifty-three participants contributing 4,369 person-visits (unit of analysis) in the United States enrolled in the Chronic Kidney Disease in Children (CKiD) Study from 2005 to 2019. Exposures: Health insurance (private vs public vs none) and dental insurance (presence vs absence) self-reported at annual visits. Outcomes: Self-reported suboptimal health care utilization in the past year, defined separately as not visiting a private physician, visiting the emergency room, visiting the emergency room at least twice, being hospitalized, and self-reported suboptimal dental care utilization over the past year, defined as not receiving dental care. Analytical Approach: Repeated measures Poisson regression models were fit to estimate and compare utilization by insurance type and disease severity at the prior visit. Additional unadjusted and adjusted models were fit, as well as models including interactions between insurance and Black race, maternal education, and income. Results: Those with public health insurance were more likely to report suboptimal health care utilization across the CKD severity spectrum, and lack of dental insurance was strongly associated with lack of dental care. These relationships varied depending on strata of socioeconomic status and race but the effect measure modification was not significant. Limitations: Details of insurance coverage were unavailable; reasons for emergency care or type of private physician visited were unknown. Conclusions: Pediatric nephrology programs may consider interventions to help direct supportive resources to families with public insurance who are at higher risk for suboptimal utilization of care. Insurance providers should identify areas to expand access for families of children with CKD.